“Exposing force”: the COVID-19 pandemic and women's sport in Ireland during 2020–2021 - Crosson, Seán; Ní Chumhaill, Maedhbh (Frontiers in Sports and Active Living, 2023)
The Covid-19 pandemic revealed structural and ongoing issues with regard to the manner in which women’s sports are facilitated and promoted, including in Ireland. Irish Times journalist Una Mullally (2020) argues that the pandemic acted as an ‘exposing force’ that highlighted the inadequacies of health and other organisational infrastructures, services and supports in an Irish society weakened by years of neoliberal orthodoxy. Here we borrow the term ‘exposing force’ to trace how the pandemic served to highlight neglected weaknesses and inequalities with regard to the structures and supports available to facilitate women’s sport in Ireland compared to men’s equivalent sports. Our findings are primarily informed by a survey conducted in June and July of 2021 with 194 female athletes across the island of Ireland. The athletes surveyed were engaged primarily with the indigenous Irish sports of camogie and Ladies Gaelic football, and (to a lesser extent) hockey and rugby, and each responded to a 28-question survey. Our findings indicate that the experiences of female athletes during the Covid-19 pandemic raise serious questions regarding equality in sport across gender lines. Concerns expressed by the surveyed athletes, especially in relation to access to facilities, inadequate sponsorship, and funding reveal salient aspects of the experiences of Irish female athletes during the pandemic, and its role as an ‘exposing force’ of inequalities within Irish sport.